2014
DOI: 10.1038/cddis.2014.162
|View full text |Cite
|
Sign up to set email alerts
|

Impaired autophagic flux is associated with increased endoplasmic reticulum stress during the development of NAFLD

Abstract: The pathogenic mechanisms underlying the progression of non-alcoholic fatty liver disease (NAFLD) are not fully understood. In this study, we aimed to assess the relationship between endoplasmic reticulum (ER) stress and autophagy in human and mouse hepatocytes during NAFLD. ER stress and autophagy markers were analyzed in livers from patients with biopsy-proven non-alcoholic steatosis (NAS) or non-alcoholic steatohepatitis (NASH) compared with livers from subjects with histologically normal liver, in livers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
390
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 504 publications
(445 citation statements)
references
References 50 publications
24
390
1
3
Order By: Relevance
“…It has already been reported that HFD feeding induced the activation of the unfolded protein response (UPR) related to reticulum stress [79]. In fact, in the present study HFD increased the gene expression of the ER stress markers GRP78 and CHOP, similarly to findings shown in patients whith NAFLD [80]. Quercetin supplementation to HFD-fed mice reverted gene expression deregulation associated to this stress pathway.…”
Section: Thus Quercetin Reduced the Increased Firmicutes/bacteroidetessupporting
confidence: 74%
See 1 more Smart Citation
“…It has already been reported that HFD feeding induced the activation of the unfolded protein response (UPR) related to reticulum stress [79]. In fact, in the present study HFD increased the gene expression of the ER stress markers GRP78 and CHOP, similarly to findings shown in patients whith NAFLD [80]. Quercetin supplementation to HFD-fed mice reverted gene expression deregulation associated to this stress pathway.…”
Section: Thus Quercetin Reduced the Increased Firmicutes/bacteroidetessupporting
confidence: 74%
“…The beneficial effect of quercetin on reticulum stress could be exerted by a complex mechanism underlying its modulatory effect on dysbiosis-mediated gut-liver axis activation and also by counteracting FFA and CYP2E1-dependent lipotoxicity as a result of its antioxidant activity, as previouly suggested [81]. The blockage of reticulum stress by quercetin could be relevant in the progression of steatosis to steatohepatitis, given its central role in the pathogenesis of NAFLD [80].…”
Section: Thus Quercetin Reduced the Increased Firmicutes/bacteroidetesmentioning
confidence: 99%
“…In livers from patients with nonalcoholic fatty liver disease or nonalcoholic steatohepatitis, there was increased ER stress gene expression with decreased autophagic flux (112). Consistently, palmitate treatment in Huh7 cells increased ER stress associated with decreased autophagy, which was restored with an autophagy inducer, rapamycin (112).…”
Section: Heartmentioning
confidence: 53%
“…Densitometry analysis of the proteins was performed for each sample. www.impactjournals.com/oncotarget (PI3K) inhibitor, was used to block autophagy because the complex of Beclin-1 and PI3K is required for autophagic vesicle nucleation [17]. As reported in a previous study [18][19][20][21], less apoptotic cells were observed in mice treated with CCl 4 and ALR than those treated with CCl 4 only, which suggested that ALR inhibits hepatocyte apoptosis.…”
Section: Alr Suppresses Hepatocyte Apoptosis In Mice With CCL 4 -Indumentioning
confidence: 70%